2006
DOI: 10.1111/j.1467-629x.2006.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting graduates' perceptions of skills emphasis in undergraduate courses: an investigation from two Victorian universities

Abstract: This study investigated the emphasis placed on technical and generic skills developed during undergraduate accounting courses from the graduate perspective. It is motivated by two issues. First, calls by the accounting profession and international education committees regarding the professional adequacy of graduates. Second, the challenge facing educators and professional bodies to design accounting courses that address a diverse range of needs from students, the educational philosophy of the institution, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
0
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(185 citation statements)
references
References 41 publications
6
167
0
12
Order By: Relevance
“…Therefore, we can say that professional accountants consider these skills as implicit; their presence in the skills base of accounting graduates is quite obvious. This finding corroborates the results of researches conducted in other contexts such as the United States (Gabric and MacFadden, 2001) and Australia (De Lange et al, 2006;Kavanagh and Drenan, 2008;Kavanagh et al, 2009). To better summarize the items and to reduce the complexity of our analysis, further data analysis was conducted.…”
Section: Employer Perceptionssupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, we can say that professional accountants consider these skills as implicit; their presence in the skills base of accounting graduates is quite obvious. This finding corroborates the results of researches conducted in other contexts such as the United States (Gabric and MacFadden, 2001) and Australia (De Lange et al, 2006;Kavanagh and Drenan, 2008;Kavanagh et al, 2009). To better summarize the items and to reduce the complexity of our analysis, further data analysis was conducted.…”
Section: Employer Perceptionssupporting
confidence: 82%
“…The individual items for generic and technical skills and attributes were based on the literature (Albrecht and Sack, 2000;Gabric and McFadden, 2001;De Lange et al, 2006;Kavanagh et Drenan, 2008;Kerlan, 2000;Yaich, 2005;Goleman, 1999;Mathews et al, 1990) as well as on the Accounting Course Requirements in Tunisia. Minor refinements were made for the Tunisian context and to include points recommended by students and professionals through the qualitative phase (Note 6) which allows us to compile a list consisting of 78 items divided into seven categories: (1) Technical skills (accounting, financial and tax), (2) management skills, (3) IT skills,(4) Physical qualities, (5) Intellectual skills, (6) Interpersonal skills and (7) Personal skills.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…According to the general rule applied in most factor analysis studies (De Lange et al (2006); Kavanagh and Drennan, (2008);Lin, (2008)) skills with commonalities of greater than 0.51 are included, otherwise the item is excluded on the basis of its low loading. The criterion for the number of factors to be extracted is based on the eigenvalue of one and each factor of the survey has exceeded the acceptable level (0.6) of reliability Cronbach' α (Field, 2009) As a result, five factors were extracted with 70.47 % of the total variance being explained cumulatively.…”
Section: International Journal Of Accounting and Financial Reportingmentioning
confidence: 99%
“…Abayadeera and Watty (2016:p149) define generic skills as those capabilities required by graduate accountants for employability and career advancement. Other authors De Lange, Jackling, and Gut (2006) referred to generic skills as the skills that capture transferrable qualities to suit the industry in which graduates work; these include but are not limited to, communication, team skills, leadership, problem solving, analytical and interpersonal skills.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, De Lange, Jackling, and Gut (2006) found that the accounting curriculum has failed to provide skilled and well-equipped professional accountants according to the needs of the market, despite strong demand for specialized manpower. While, the employers are seeking a diverse range of skills and attributes in new graduates in order to maintain a competitive advantage, despite the fact that many countries are facing skill shortage in the area (Birrell, 2006).…”
mentioning
confidence: 99%